A three-dimensional fluid-structure interaction model based on SPH and lattice-spring method for simulating complex hydroelastic problems - Ng, K.C.; Low, W.C.; Chen, Hailong; Tafuni, A.; Nakayama, A. (Elsevier Ltd, 2022)
The present work revolves around the development of a 3D particle-based Fluid-Structure Interaction (FSI) solver to simulate hydroelastic problems that involve free surface. The three-dimensional Volume-Compensated Particle Method (VCPM) for modelling deformable solid bodies is developed within the open-source SPH software package DualSPHysics. Complex 3D FSI problems are readily simulated within a reasonable time frame thanks to the parallel scalability of DualSPHysics on both CPU and GPU. The Sequential Staggered (SS) scheme paired with a multiple time-stepping procedure is implemented in DualSPHysics for coupling the SPH and VCPM models. It is found that the SPH-VCPM method is computationally more efficient than the previously reported SPH-TLSPH method. Extensive validations have been performed based on some very recent 3D experimental setups that involve violent free surface and complex structural dynamics. Findings from this research highlight the capability of the 3D SPH-VCPM model to reproduce some of the physical observations that were not captured by previous 2D studies. Some preliminary 3D FSI results involving solid fracture are also demonstrated.